The Effects of using Pictures on EFL Learners’ Vocabulary Retention - Na, Dao Ra Ta; Trang, Nguyen Huynh (International Journal of Emerging Trends in Social Sciences, 2022)
Innovation is necessary for improvement. This inspirational saying triggered the author to try new things for enhancement. This study explored the effect of using pictures to instruct vocabulary in EFL classrooms. At the same time, the EFL students’ attitudes toward this instruction were also examined. To have the data for the study, a group of 70 seventh-graders at Duyen Hai Ethnic Boarding Junior High School in Tra Vinh province were recruited as participants. The study had two parts. The first part of the study dealt with the intervention of vocabulary instruction in the two groups of students. 35 students were chosen for the experimental group, and the other 35 for the control group. The experimental group was exposed to vocabulary instruction with pictures while the control group was taught with the traditional vocabulary teaching method (without using pictures). Both groups had undergone the pretest, posttest, and delayed tests. The results showed that both groups’ scores on vocabulary tests improved, but the experimental group’s scores were higher than that of its counterparts. Then, the study also had the result of the experimental students’ attitudes toward the intervention of using pictures to teach vocabulary. They had a positive attitude toward this teaching strategy. Finally, based on the results of the study, some suggestions and limitations of the study were proposed.